Effect of constraints on Tiebout competition: Evidence from the Michigan school finance reform - Rajashri Chakrabarti; Joydeep Roy (Federal Reserve Bank of New York, 2010)
This paper examines the effects of constraints in a Tiebout framework applied to school finance reforms. We use data from Michigan, which enacted a comprehensive school finance reform in 1994 that, in effect, ended local discretion over school spending. This scenario affords us a unique opportunity to study the implications of imposing limits on local government's control over the quality of local public goods. We find that the reform was successful in overturning existing trends toward increased disparities. However, the reform also constrained the highest spending districts and was associated with negative effects on their subsequent educational outcomes. These results survive several sensitivity checks. Going behind the black box to look at whether the reform affected incentives and responses, we find that loss of discretion appeared to act as a strong disincentive to high-spending districts and, more generally, across the board. The performance improvements of the lowest spending districts were likely related to relative increases in spending rather than higher effort. This same finding is corroborated by results from an alternative strategy, which exploits differences in the nature of incentives faced by districts in more competitive areas versus those in less competitive areas.
Keywords: H4; I2; 330; Tiebout; school finance; incentives; competition